Perancangan Video Animasi 2D tentang Mengenal Realfood untuk Pembelajaran Anak Usia Dini - Krisna Fatichal Septiandra; Diana Aqidatun Nisa; Aileena Solicitor.C.R.E.C (UNIVERSITAS STEKOM, 2025)
Abstract. This study originates from the low awareness among early childhood learners regarding the importance of consuming nutritious and minimally processed Real Food. The purpose of this design project is to create an engaging educational medium in the form of a 2D animation titled “Kebun Imajinasi: Teman Realfoodku” to introduce the concept of Real Food to five-year-old children. A mixed-method approach (qualitative and quantitative) was applied through observation, interviews, and questionnaires involving children, parents, and professional animators. The collected data served as the foundation for designing characters, storylines, illustration styles, colors, and audio suitable for young audiences. The results show that 2D animation featuring bright visuals, playful characters, and educational narration effectively increases children’s interest and understanding of healthy food. The implication of this study highlights the potential of animation as an effective visual communication tool to promote nutritional education and healthy lifestyle habits from an early age.